Vybrané účetní a daňové aspekty zaměstnaneckých benefitů - Papežová, Martina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Bakalářská práce se zaměřuje na problematiku účetních a daňových aspektů zaměstnaneckých benefitů ve vztahu k zaměstnavateli. Zabývá se analýzou benefitů poskytovaných zaměstnavatelem a zkoumá jejich účetní a daňový dopad. Následně navrhuje způsoby zlepšení firemní politiky benefitů.

The bachelor thesis is focused on the accounting and tax aspects of employee benefits in relation to the employer. It deals with the analysis of the benefits provided by the employer and examines their accounting and tax impact. It then proposes ways to improve the benefits policy.
Selected Accounting and Tax Aspects of Emploee Benefits
Keywords: daňová povinnost; účetní aspekty; zaměstnanecké benefity; motivace; tax liability; accountant aspects; employee’s benefit; motivation